PENENTUAN INTERVAL WAKTU PERAWATAN MESIN INJECTION MOULDING MENGGUNAKAN METODE RCM DI PT “X” - Alfian Muhtadi; Etik Puspitasari (INFO-TEKNIK, 2021)
In the industrialized world, product is the main of a production process that forms a production process system. In order to a system of production process running continuesly, need a maintenance of the equipment and production machines. The machine maintenance is needed to minimize the damage of machine then the machine can be used for a long time. The purpose of the study is to calculate the reliability value in which the interval time of maintenance will be determined so that it can support the reliability of the tool. Method of the study uses the RCM (Reliability Centered Maintenance) to solve machine maintenance problems that often occur at PT “X”. RCM method has the advantage of defining a machine focused maintenance program and avoids unnecessary maintenance activities by specifying appropriate maintenance intervals. This study also presents qualitative data in the form of FMEA analysis (Failure Mode Effect Analysis) and quantitative data in the form of determining reliability values and determining maintenance time intervals which provide a solution for PT. “X”.The result of the study, reliability value of the MJM-JLB-HQ Injection Moulding Machine is 0.9183 at 12 hours, VICTOR Injection Moulding is 0.9243 at 4 hours, and the reliability value of MJM-JLB 198-HQ Mould is 0.5125 at 96 hours, VICTOR's Mould is 0.5063 at 72 hours. For the results of maintenance interval to keep the value of reliability not going down below 0.9 is 12 hours for MJM-JLB198-HQ Injection Molding Machines, then 4 hours for VICTOR Injection Moulding Machines. The result maintenance interval analysis of mould with reliability not going down below the value of 0.5 is 96 hours on MJM-JLB198-HQ Injection Moulding Machine, and 72 hours at VICTOR Injection Moulding Machine.